2019
DOI: 10.1186/s12958-019-0531-6
|View full text |Cite
|
Sign up to set email alerts
|

Contraceptive efficacy of sperm agglutinating factor from Staphylococcus warneri, isolated from the cervix of a woman with inexplicable infertility

Abstract: BackgroundVoluntary control of fertility is of paramount importance to the modern society. But since the contraceptive methods available for women have their limitations such as urinary tract infections, allergies, cervical erosion and discomfort, a desperate need exists to develop safe methods. Vaginal contraceptives may be the answer to this problem, as these are the oldest ways of fertility regulation, practiced over the centuries. With minimal systemic involvement, these are also the safest. Natural substa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Subsequently, it was found that this factor also inhibits mitochondrial Mg 2+ -ATPase activity [ 26 ]. Similarly, a sperm agglutinating factor (SAF) was previously isolated from S. warneri and its recombinant version was recently proved as spermicidal in vitro, but also as an excellent contraception in vivo [ 27 ]. As mitochondrial membrane potential may predict 4-h sperm motility [ 28 ], intact mitochondria are an essential factor of sperm motion.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, it was found that this factor also inhibits mitochondrial Mg 2+ -ATPase activity [ 26 ]. Similarly, a sperm agglutinating factor (SAF) was previously isolated from S. warneri and its recombinant version was recently proved as spermicidal in vitro, but also as an excellent contraception in vivo [ 27 ]. As mitochondrial membrane potential may predict 4-h sperm motility [ 28 ], intact mitochondria are an essential factor of sperm motion.…”
Section: Discussionmentioning
confidence: 99%
“…Pant et al. isolated an 80 kDa sperm agglutination factor from Staphylococcus warneri ; it also inhibits Mg 2+ -dependent ATPase activity and showed a potent contraceptive effect in mouse models ( Pant et al., 2019 ). Ohri et al.…”
Section: Types and Pathogenic Properties Of The Semen Microbiomementioning
confidence: 99%
“…These data indicate that the Mg 2+ -dependent ATPase plays an important role on sperm motility function. Pant et al isolated an 80 kDa sperm agglutination factor from Staphylococcus warneri; it also inhibits Mg 2+ -dependent ATPase activity and showed a potent contraceptive effect in mouse models (Pant et al, 2019). Ohri et al isolated a 70 kDa protein from the cell culture of S. aureus; this protein mediates a tail-to-tail agglutination of spermatozoa (Ohri and Prabha, 2005).…”
Section: Spermicidal Effect Of Other Pathogensmentioning
confidence: 99%
“…In the meantime, P fimbriae often found in E. coli strains during acute prostatitis [ 62 ] recognizes a-D-galp-l-4-9-D-galp (gal gal) located primarily in the sperm tail [ 65 ]. In the case of G + bacteria, particularly staphylococci, a group of proteins called microbial surface components recognize adhesive matrix molecules target proteins in the host’s extracellular matrix [ 59 ] and induce a strong affinity to selected hydrophobic molecules once the adhesion process is initiated [ 66 ]. A particular colonization advantage in staphylococci is provided by the so-called moonlight proteins that act as particularly resilient adhesins [ 59 , 67 ].…”
Section: Discussionmentioning
confidence: 99%